2020
DOI: 10.1021/acs.jpclett.0c02192
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Probing of Cholesterol-Rich Domains in Single Bilayer Dimyristoyl-Phosphocholine Membranes Using Near-Field Spectroscopic Imaging

Abstract: Cholesterol is believed to induce the formation of membrane domains, “rafts”, which are implicated in a range of natural and pathologic membrane processes. Therefore, it is important to understand the role that cholesterol plays in the formation of these structures. Here, we use label-free spectroscopic imaging to investigate cholesterol fractioning in supported bilayer membranes at nanoscale. Scattering-type scanning near-field optical microscopy (s-SNOM) was used to visualize the formation of cholesterol-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The interferometric recording of the scattered light provides infrared spectra at a spatial resolution approximately equivalent to that of the tip (20 nm) [21–28] . sSNOM has been used for the analysis of polymeric thin film surfaces, [24,29–35] imaging of cells, [36–40] viruses [41,42] and neurons [43] and the structural elucidation of protein fibrils [44–46] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interferometric recording of the scattered light provides infrared spectra at a spatial resolution approximately equivalent to that of the tip (20 nm) [21–28] . sSNOM has been used for the analysis of polymeric thin film surfaces, [24,29–35] imaging of cells, [36–40] viruses [41,42] and neurons [43] and the structural elucidation of protein fibrils [44–46] …”
Section: Introductionmentioning
confidence: 99%
“…The interferometric recording of the scattered light provides infrared spectra at a spatial resolution approximately equivalent to that of the tip (20 nm). [21][22][23][24][25][26][27][28] sSNOM has been used for the analysis of polymeric thin film surfaces, [24,[29][30][31][32][33][34][35] imaging of cells, [36][37][38][39][40] viruses [41,42] and neurons [43] and the structural elucidation of protein fibrils. [44][45][46] Although the secondary structure of protein fibrils has been successfully studied by sSNOM, in supramolecular gels the selfassembly of the gelator molecules (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Examples are the characterization of thin lms and blends, 22,23 single type and core-shell polymer nanoparticles, 21,24 multilayer structures, 25 phospholipid membranes and the distribution of cholesterol within them as well as viruses. 21,[26][27][28] Nano-FTIR spectra comply well with references from macroscopic IRtechniques and are thus suited for library-based identication. 20,23,27,29 Methodological and theoretical details of scattering-type scanning near eld optical microscopy (s-SNOM) and nano-FTIR are explained in ref.…”
Section: Introductionmentioning
confidence: 69%
“…By depositing the sample on the epitaxial graphene on a SiC substrate, the authors found that the near-field graphene plasmon map is a good indicator with enhanced image contrast at domain boundaries. In parallel, near-field spectroscopic visualization of cholesterol-rich domains at the bilayer of 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) was conducted by s-SNOM [100]. Three nano domains with different cholesterol concentrations -phaseseparated cholesterol-rich domains, cholesterol-poor DMPC bilayer, and cholesterol-rich DMPC bilayer, were discovered, confirming the optimal mixture ratio of cholesterol/DMPC to be 15/85.…”
Section: S-snom In the Characterization Of Biomoleculesmentioning
confidence: 83%